The BIS and the Latin American debt crisis of the 1980s - Piet Clement; Ivo Maes (National Bank of Belgium, 2013)
The Latin American debt crisis, which broke out in August 1982, was the first global financial crisis in the postwar period. While the crisis started in the "periphery", it constituted a threat to the "core" of the world economy, as the banking system was under severe pressure. Alongside the IMF, the BIS played an important role in coordinating the international response to the crisis. Moreover, a lot of work at the BIS in the second half of the 1970s had aimed at restraining the debt build-up. Discussions on the rising debt levels were highly influential in shaping the BIS view of financial stability, with the "macroprudential" concept at its core. However, in the analysis of the debt buildup, the role of financial innovations was not really captured. In this paper, we focus on the Latin American debt crisis, discussing first the debt build-up, different initiatives to restrain lending and the BIS role in the management of the crisis. We then turn to the ensuing efforts to strengthen the financial system and the emerging BIS approach to financial stability.
Keywords: A11; B22; B32; E3; F02; G10; N10; 330; Latin American debt crisis; BIS; macroprudential; financial fragility; Lamfalussy; Schuldenkrise; Finanzmarktaufsicht; Lateinamerika